Effect of feeding frequency on total bilirubin reduction and body temperature changes among neonates with jaundice receiving blue led phototherapy at Marthen Indey TNI-AD Hospital, Jayapura - Sumiyati Sumiyati; Yuli Peristiowati; Ratna Wardani (Politeknik Negeri Subang, 2026)
Background: Hyperbilirubinemia in neonates requires prompt intervention to prevent neurological complications. Blue LED phototherapy is a primary treatment, yet its effectiveness relies on hydration and feeding frequency to facilitate bilirubin excretion. Phototherapy also carries a risk of altering body temperature, necessitating close monitoring. Purpose: This study analyzed the effect feeding frequency and blue LED phototherapy with total bilirubin reduction and body temperature changes among neonates with jaundice. Methods: A quasi-experimental pretest-posttest comparison group study involved 80 neonates selected through purposive sampling. Respondents were divided into high feeding frequency (10 times/24 hours, n=40) and low feeding frequency (6 times/24 hours, n=40) groups. Total bilirubin levels and body temperature were measured before and after 24-hour therapy. Analyses included the Wilcoxon Signed Rank Test and Mann-Whitney U Test. Results: Neonates had a mean gestational age of 38.79 ± 1.10 weeks, and birth weight of 2749.7 ± 166.3 g. Baseline total bilirubin (15.52 ± 0.31 mg/dL) and body temperature (36.75 ± 0.09°C) were comparable between groups. Both groups showed significant bilirubin reduction (p < 0.001). The high-frequency group demonstrated significantly greater reduction (median change 5.95 mg/dL) than the low-frequency group (3.40 mg/dL; p < 0.001, r = 0.62). Temperature changes within both groups were significant (p < 0.001) but remained clinically normal, with no between-group difference (p = 0.176, r = 0.14). Conclusion: Higher feeding frequency was associated with greater bilirubin reduction without adverse temperature effects. However, the quasi-experimental design limits causal inference. Clinical protocols should emphasize frequent feeding and temperature monitoring for safe, optimal treatment.